2016
DOI: 10.1016/j.celrep.2016.02.060
|View full text |Cite
|
Sign up to set email alerts
|

Uridylation and PABP Cooperate to Repair mRNA Deadenylated Ends in Arabidopsis

Abstract: Uridylation emerges as a key modification promoting mRNA degradation in eukaryotes. In addition, uridylation by URT1 prevents the accumulation of excessively deadenylated mRNAs in Arabidopsis. Here, we show that the extent of mRNA deadenylation is controlled by URT1. By using TAIL-seq analysis, we demonstrate the prevalence of mRNA uridylation and the existence, at lower frequencies, of mRNA cytidylation and guanylation in Arabidopsis. Both URT1-dependent and URT1-independent types of uridylation co-exist but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 39 publications
6
58
0
Order By: Relevance
“…TAIL‐seq was decisive to demonstrate and generalize a link between uridylation and degradation of mRNAs. Firstly, TAIL‐seq revealed that mRNA uridylation is widespread in human cells, a conclusion later extended to Arabidopsis . Secondly, uridylation of human mRNAs by TUT4/7 tags is preceded by deadenylation, confirming at a transcriptome‐wide level previous observations made in A. nidulans and Arabidopsis for candidate mRNAs .…”
Section: Uridylation Of Mrnas: Decay and Other Consequencessupporting
confidence: 75%
See 1 more Smart Citation
“…TAIL‐seq was decisive to demonstrate and generalize a link between uridylation and degradation of mRNAs. Firstly, TAIL‐seq revealed that mRNA uridylation is widespread in human cells, a conclusion later extended to Arabidopsis . Secondly, uridylation of human mRNAs by TUT4/7 tags is preceded by deadenylation, confirming at a transcriptome‐wide level previous observations made in A. nidulans and Arabidopsis for candidate mRNAs .…”
Section: Uridylation Of Mrnas: Decay and Other Consequencessupporting
confidence: 75%
“…Although, URT1‐mediated uridylation does not seem to affect the rate of mRNA decay, it participates in establishing the 5′→3′ polarity of mRNA degradation (Figure ) which could be essential during co‐translational decay . A second TUTase, yet to be formally identified, does not prevent excessive deadenylation and may promote RNA decay . Intriguingly, in vitro assays using human cell extracts also reported that uridylation favors decapping while conferring protection of the 3′ end, likely through binding of the LSm1‐7 complex .…”
Section: Uridylation Of Mrnas: Decay and Other Consequencesmentioning
confidence: 99%
“…We also did not consider nuclear mechanisms of transcript turnover that can involve CBP80 . Nor did we consider N 6 -methyladenosine and other modifications of specific nucleotides (the epitranscriptome; Luo et al, 2014;Vandivier et al, 2015;Zuber et al, 2016;David et al, 2017), which may influence RNA-protein interactions and, hence, the nuclear or cytoplasmic fates of individual transcripts. The wealth of new discoveries of the dynamic cytoplasmic mRNP triumvirate has unearthed new challenging questions (see Outstanding Questions) that may provide insights relevant to other eukaryotes or of value to crop improvement.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, yeast mutants in decapping and deadenylation, respectively, display an increase in oligouridylated mRNAs indicating that uridylation acts upstream of both decapping and deadenylation in S. pombe [69]. The bypass of deadenylation in mRNA degradation in S. pombe might occur owing to its relatively short poly(A)-tails (the median is 28 nt) compared with other eukaryotes [42,77]. The median poly(A)-tail length for mammalian cells is 50 -100 nt, 51 nt for Arabidopsis leaves and 50 nt for Drosophila S2 cells [7,77].…”
Section: (A) Uridylation-mediated Mrna Decapping and Decaymentioning
confidence: 99%
“…In contrast to S. pombe, in mammals and plants uridylation was mostly observed on partially or fully deadenylated 3 0 ends [7,42]. Shortening of poly(A)-tails is an integral step in the decay of poly(A)þ mRNAs.…”
Section: U U a A A A A A A A A A A A A A A A A A A A A A A A A A A A mentioning
confidence: 99%